Toxicity assessment of gelsenicine and the search for effective antidotes. (7th January 2022) - Li, Yu-Juan; Yang, Kun; Long, Xue-Ming; Xiao, Gang; Huang, Si-Juan; Zeng, Zi-Yue; Liu, Zhao-Ying; Sun, Zhi-Liang
Background: Gelsenicine, one of the most toxic alkaloids of Gelsemium elegans Benth ( G. elegans ), causes severe respiratory depression. However, its toxicity mechanisms are yet to be elucidated and no effective antidotes are available. Objective: This study aimed to analyse the toxicity characteristics of gelsenicine. Methods: Both acute and sub-acute toxicities were evaluated. Gelsenicine distribution and elimination in the central nervous system (CNS) and blood were observed. Effective antidotes for gelsenicine poisoning were screened. Results: In the acute toxicity study, gelsenicine was highly toxic, and female rats exhibited greater sensitivity to gelsenicine than male rats (LD50 0.520 mg/kg vs 0.996 mg/kg, respectively). Death was primarily caused by respiratory failure. However, in the sub-acute toxicity study, no significant organ damage was observed. Gelsenicine was easily absorbed from the gastrointestinal tract and penetrated the blood–brain barrier, reaching peak concentrations in the CNS within 15 min and rapidly decreasing thereafter. Flumazenil or diazepam combined with epinephrine reversed gelsenicine toxicity and significantly improved survival rate in mice. Conclusions: Gelsenicine is a highly toxic substance that affects nerve conduction without causing damage; the potential toxic mechanism is possibly associated with GABAA receptors. Our findings provide insights into the clinical treatment of gelsenicine - related poisoning and its toxicity mechanisms.